ESRA19-0071 Ultrasound-guided bilateral modified thoracolumbar interfascial plane or infiltration block for analgesia after lumbar spinal surgery: a prospective randomized open blinded end-point study. (30th August 2019) - Ueshima, H; Hiroshi, O
Abstract : Background and aims: Bilateral modified thoracolumbar interfascial plane (TLIP) block provides effective analgesia for spinal surgery. Although an ultrasound machine is needed to provide effective modified TLIP block, is not needed for an infiltration block. We examined patients undergoing lumbar spinal surgery for comparing analgesic efficacy between bilateral modified TLIP and the infiltration blocks. Methods: 60 adult patients scheduled for lumbar spinal surgery were randomly allocated to receive bilateral modified TLIP block (T group) or infiltration block (I group) under general anaesthesia. the primary outcome was cumulative fentanyl administered for rescue analgesia, and secondary outcomes were the number of demands for rescue analgesia and successfully delivered rescue analgesia; pain scores on the visual analogue scale (VAS) at rest and during mobilisation; and extent of sensory level block during the first 48 hours after surgery. Results: 29 patients in the T group and 30 patients in the I group were evaluated. Cumulative fentanyl consumption for rescue analgesia (mean [sd]); T group, 83.2 [60.6] μg; I group, 287.3 [75.3] μg) and the number of demands for rescue analgesia and successfully delivered rescue analgesia, and VAS scores (since 2 hours postoperatively at rest and 6 hours postoperatively during mobilisation) were lower in T group than in I group (P<0.001).The extent of sensory level block in T group remained constant during the first 12 hours after surgery, but reduced gradually in I group after the first 2 hours following surgery. Conclusions: Compared with infiltration block, bilateral modified TLIP block may provide effective analgesia for patients undergoing lumbar spinal surgery under general anaesthesia.